Hubungan Antara Persepsi Terhadap Lingkungan Kerja Dengan Motivasi Kerja Pada Pegawai Balaikota Surakarta - Viana, Hernia Tut, Achmad Dwityanto, S.Psi, M.Si (2017)
The aim of this research is to know the relationship between perception of work environment with work motivation on the Town Hall employees. The hypothesis proposed that there are positive relationship between perception of work environment with work motivation on the Town Hall employees. Sampling technique is used in this research was technique of purpovise sampling, there are 90 respondents. .These research used quantitative methods with perception of work environment and work motivation scale. Research on data analysis using SPSS 19.00 with product-moment correlation, the correlation coefficient value of acquired 0.612; p = 0.000 (p < 0.01) which showed that there is a positive relationship between perception of work environment with work motivation. The effective contribution of these two variables is indicated by a value of r2 = 0.374 it means that the perception of work environment variables affects by 37,4% to work motivation and there is 62,6% is influenced by other factors perception of work environment. Perception of work environment relatively high with empirical mean (RE) of 90.79 and average hypothetical (RH) of 72.5. While, work motivation relatively high with average empiric (RE) of 91.16 and average hypothetical (RH) of 72.5.